2016
DOI: 10.1177/1937586715619741
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Brief Nature Sound Intervention on Muscle Tension, Pulse Rate, and Self-Reported Stress

Abstract: This study highlights the potential benefit of even very brief (less than 7 min) exposure to nature sounds. Brief nature sound "booster breaks" are a promising area for future research with important practical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…It works even with indoor exposure to nature photographs, potted plants or window views, but is more clearly effective in the outdoors. The same benefits are reported by both staff and patients, which is confirmed by objective measures of tension (including BP, heart rate, and electromyography), 11 and the benefits are almost immediate. Only in the Intensive Care Unit is no benefit seen, 9 which is hardly surprising.…”
Section: Environment "Why Don't You Have a Big Fish-tank Like The Prasupporting
confidence: 60%
“…It works even with indoor exposure to nature photographs, potted plants or window views, but is more clearly effective in the outdoors. The same benefits are reported by both staff and patients, which is confirmed by objective measures of tension (including BP, heart rate, and electromyography), 11 and the benefits are almost immediate. Only in the Intensive Care Unit is no benefit seen, 9 which is hardly surprising.…”
Section: Environment "Why Don't You Have a Big Fish-tank Like The Prasupporting
confidence: 60%
“…Furthermore, since waiting spaces were perceived by many not to be engaging, playing calming music or nature sounds in waiting rooms may be a quick and easy intervention to benefit patients, even while other types of additions are being developed to enhance the space. This kind of audio is well-demonstrated to decrease anxiety in waiting patients [4,11].…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have reported that listening to nature sounds during the intra‐operative period resulted in lower heart rate and blood pressure (Tsuchiya et al , ; Arai et al , ). Nature sounds have also been found to decrease pulse rate, muscle tension, and stress in healthy volunteers (Largo‐Wight et al , ). Studies have found evidence to indicate that nature sounds reduce anxiety in patients undergoing sigmoidoscopy or mechanical ventilation and those being weaned from mechanical ventilation (Lembo et al , ; Saadatmand et al , ; Aghaie et al , ).…”
Section: Introductionmentioning
confidence: 99%